Democracy by Disclosure : The Rise of Technopopulism - Graham, Mary, 1944- (Book collections on Project MUSE., 2002)
"In December 1999, the Institute of Medicine shocked the nation by reporting that as many as 98,000 Americans died each year from mistakes in hospitals - twice the number killed in auto accidents. Instead of strict rules and harsh penalities to reduce those risks, the institute called for a system of standardized disclosure of medical errors. If it worked, it would create economic and political pressures for hospitals to improve their practices." "Since the mid-1980s, Congress and state legislatures have approved scores of new disclosure laws to fight racial discrimination, reduce corruption, and improve services. The most ambitious systems aim to reduce risks of everyday life - risks from toxic pollution, contaminants in drinking water, excess fat in packaged foods, lead paint, workplace hazards, and SUV rollovers. Unlike traditional government warnings, they require corporations and other organizations to produce standardized factual information at regular intervals about health, safety, or environmental threats they create. Legislated transparency has become a mainstream instrument of social policy."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved